#### Answer

$F(y) = $ $y^{-2} +c$

#### Work Step by Step

$f(y)=\frac{-2}{y^3}$
$f(y)= -2y^{-3}$
$\int f(y)dy = -2\int y^{-3}$
$F(y)= -2\int \frac{y^{-2}}{-2}$
$F(y) = $ $y^{-2} +c$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$F(y) = $ $y^{-2} +c$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.